Analisis Kondisi Peralatan Unit Kerja Aviation Security Dalam Menunjang Keamanan Dan Keselamatan Penerbangan Di Security Check Point 1 Dan 2 Bandar Udara Abdulrachman Saleh Malang - Muhammad Syafiuddin Sholiha (INSOLOGI: Jurnal Sains dan Teknologi, 2022)
The condition of avsec work unit equipment located in SCP 1 and 2 is very important for flight safety and security. Equipment that is in good condition and suitable for use according to the SOP applied will assist Avsec officers in carrying out their duties in SCP 1 and 2 as flight security and safety guards. The purpose of this study is to find out and qualitatively analyze the condition of Avsec work unit equipment in SCP 1 and 2 and the application of SOPs to the feasibility of Avsec equipment and the impact of equipment that has been damaged or errord to aviation safety and security at Abdulrahcman Saleh Malang Airport. This research uses qualitative research methods. Data sources come from primary and secondary data. Data collection techniques used are observation, interviews and documentation. The results showed that the condition of Avsec work unit equipment in the SCP 1 and 2 areas was good and not good. Abdulrachman Saleh Malang Airport still does not have Explonsive Detection System equipment used to detect explosives and Liquid Detectors that serve as liquid detection. Malang Airport has implemented sops on the feasibility of equipment by performing the correct operation, equipment maintenance and facility reporting. Damage or errors experienced by equipment have an impact on the inspection process is not optimal and the inspection of passengers' luggage is done manually by officers so that it can threaten the safety and security of the flight.